2020
DOI: 10.1136/bmjopen-2020-044617
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based approach on the social impact and mental health in Spain during COVID-19 lockdown: a cross-sectional study

Abstract: ObjectiveLockdown has impacts on people’s living conditions and mental health. The study aims to assess the relations between social impact and mental health among adults living in Spain during COVID-19 lockdown measures, taking a gender-based approach into account.Design, setting and participantsWe conducted a cross-sectional study among adults living in Spain during the lockdown of COVID-19 with an online survey from 8 April to 28 May 2020. The main variable was mental health measured by Generalized Anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
144
10
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(186 citation statements)
references
References 24 publications
26
144
10
6
Order By: Relevance
“…Furthermore, we highlight that our sample had a higher participation of women, although the strategy to promote the survey was targeting the general population (institutional websites announcements and calls and social network promotion targeting general population in Brazil). Despite that we noticed that others online surveys about COVID-19 also reported higher female participation [ 43 ]. Our study was conducted in Brazil, a country with continental dimensions that has been facing a political crisis that continues to increase with the rise of confirmed cases and deaths.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, we highlight that our sample had a higher participation of women, although the strategy to promote the survey was targeting the general population (institutional websites announcements and calls and social network promotion targeting general population in Brazil). Despite that we noticed that others online surveys about COVID-19 also reported higher female participation [ 43 ]. Our study was conducted in Brazil, a country with continental dimensions that has been facing a political crisis that continues to increase with the rise of confirmed cases and deaths.…”
Section: Discussioncontrasting
confidence: 56%
“…The current study also identified the role of health information as a mediator in the link between physical symptoms and the perceived impact of the pandemic. During the strict lockdown, people were refrained from social interaction 41 and spent more time at home and searching for health information online. Consistent with the protection motivation theory 19 , the need to search for more health information is triggered by activity in survival circuits that detects imminent threats of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Although men are hit harder by COVID-19 than women [ 23 ], previous studies indicated that women are more worried about the spread of the infection. In a recent Cuban population study, being female was a predictor of medium and high levels of fear of COVID-19 [ 24 ], and also in several other researches it emerged that being female is significantly associated with a greater psychological impact of the outbreak and higher levels of stress, anxiety [ 25 ], insomnia, perceived stress, adjustment disorders and depression [ 26 , 27 ]. Galasso et al (2020), in a study carried out in eight countries, showed that women are more likely to perceive COVID-19 as a very serious health problem and to agree and comply with restraining public policy measures [ 28 ].…”
Section: Discussionmentioning
confidence: 99%